Development of Edmodo-Based E-Learning Media on the Plantae's Discussion for Learning Biological High School - Ivaturrohmah .; Imam Mudakir; Kamalia Fikri (BIOEDUKASI, 2018)
Biology is a science whose concept is abstract and has a wide scope. One of them is the subject of Plantae that requires appropriate media to help to visualize the material being taught. Some things to consider in the selection of media such as material and learner characteristics. Characteristics of learners today is known as the Z generation so that the appropriate media is one that involves the use of technology. One of them is Edmodo-based e-learning media. The use of Edmodo-based e-learning media enables the delivery of more varied and much-involved students. This study aimed to find out the development process of Edmodo-based e-learning media and to produce a valid product as well as to know the effectiveness and practicality of the product. This research was a development research using a method by Borg and Gall (1983) model that has been modified by Sugiyono (2006). Stage of limited scale trial was conducted in SMAN 2 Jember and SMAN 4 Jember. The result of the product validation test of e-learning media development on average produced a valid product. Effectiveness test at SMAN 2 Jember and at SMAN 4 Jember resulted in a high N-Gain score. The result of the practicality test through the students and teachers responses of SMAN 2 Jember and SMAN 4 Jember created a response with strongly agree category. Keywords: Edmodo, e-learning, development, Plantae subject.